A study on perception of medical students regarding implementation of elective module in India - Kalpesh Vidja; Jitendra Patel; Harshul Patidar; Pratik Akhani; Parth Patel (Research and Development in Education (RaDEn), 2023)
As suggested by the National Medical Commission (NMC) of India recently, the elective module was implemented in our medical college for MBBS admission batch 2019. Since, this was the first of its kind implementation in our institute and across the country, we planned this study to know the perception of medical students regarding the implementation of elective module. We conducted a cross-sectional survey among MBBS students of 2019 batch. A pre-validated questionnaire was prepared by the Medical Education Unit (MEU) members of our institute using online Google form and was circulated to all via WhatsApp group and email. A total of 63 responses from medical students were included for data analysis. Majority students said that objectives of the elective module were largely met and the faculty members were very helpful and responsive, and that they actively participated in the electives. Majority of them agreed that it was a very good academic activity, the time duration was appropriate, and it provided an opportunity to show creativity and for teamwork. Most students rated the overall experience of electives as "good" and above, however they were worried about getting faculty signatures in the logbooks.